Self-Healing melalui Teknik Relaksasi sebagai Intervensi Kecemasan pada Remaja Korban Kekerasan Seksual: Studi Pra-Eksperimental di Munggu, Bangka Tengah - Siska Dwi Paramitha; Chitra Fraghini (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Sexual violence against adolescents leads to severe psychological consequences, particularly anxiety disorders that impair development and social functioning. This study examined the effectiveness of self-healing intervention through relaxation techniques in reducing anxiety among adolescent survivors of sexual abuse in Munggu, Central Bangka. A pre-experimental one-group pretest-posttest design was employed. Seven participants were selected using purposive sampling based on inclusion criteria. Anxiety levels were measured by the anxiety subscale of the Depression Anxiety Stress Scale 21 (DASS-21) before and after four sessions of relaxation training (diaphragmatic breathing and progressive muscle relaxation). The Wilcoxon Signed Rank test was used for data analysis. Results revealed a decrease in anxiety scores in six out of seven participants, but the difference was not statistically significant (Z = -1.859, p = .063). Despite non-significance, four participants shifted from severe to moderate anxiety categories. Qualitative findings corroborated that relaxation techniques assisted survivors in managing acute daily anxiety. The findings indicate that short-term self-healing intervention alone is insufficient to significantly alleviate trauma-based anxiety but holds promise as an adjunctive coping skill. Future research with longer intervention duration, larger sample, and control group is strongly recommended.